Pengaruh Kegiatan Mozaik terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun di TK Santo Thomas 2 Medan - Gebi Renata Tarigan; May Sari Lubis; Gita Noveri Eza; Anada Leo Virganta; Elya Siska Anggraini (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aims to determine the fine motor skills of children aged 5-6 years through mosaic activities at Kindergarten Santo Thomas 2 Medan. The method used in this research is Pre-experimental with One Group Pre-test Post-test Design. The subjects in this research were cheerful group B consisting of 20 children. Research data uses the Wilcoxon signed-rank test and is equipped with a description of the data using percentage calculations. From data analysis, it is obtained that Tcount = 192,5 with α = 0.05 Ttable = 52. Tcount > Ttable where 192,5 > 52. This means that the hypothesis which states that there is an influence of mosaic activities on children's fine motor skills is accepted. The Wilcoxon test results are complemented by motor abilities in percentage with an average pre-test score of 5.25 and post-test score of 7.2. The average score of children's fine motor skills after being given the mosaic activity was higher than before being given the mosaic activity.